Desain Tata Kelola Rekam Medis Elektronik Pelaporan Kasus Tuberculosis dengan Metode RAD (Rapid Application Development) - Najmuddin, Muhammad Naufal; Syahidin, Yuda; Sari, Irda (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
The current problem in the process of reporting Tuberculosis (TB) cases is the lack of effectiveness and efficiency in data collection and processing, which can hamper TB control efforts. In addition, poorly organized reporting also causes difficulties in monitoring the spread of TB disease and taking appropriate preventive action. The proposed method to address these issues is to apply the Rapid Application Development (RAD) method. This method allows customization and refinement of software according to the needs of users, including medical personnel and public health centers. Rapid and iterative software development, involving key stakeholders. Features that can be implemented in the software include electronic forms for patient data collection, real-time notification of TB disease spread, and structured report generation and data analysis. The results of applying the RAD method to the TB case reporting problem showed significant improvements in the efficiency and effectiveness of data collection, processing, and reporting. The system assists medical personnel in the management and monitoring of TB cases, and provides necessary information to public health centers and the Tuberculosis Disease Control Agency. With the use of RAD-based software, TB case reporting can be done more quickly, accurately, and structured, which in turn will help reduce the spread of TB disease and improve preventive measures.